Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/bjc.2014.269
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting the IGF system and HIF-1 inhibits migration and invasion by (triple-negative) breast cancer cells

Abstract: Background:Metastatic triple-negative breast cancer is mostly incurable, due to lack of suitable drug targets. The insulin-like growth factor (IGF) system could provide such a target, and IGF-1 receptor (IGF-1R)-directed agents are already available, but seem unable to control all the complexities of the system, including crosstalk with hypoxia-inducible pathways.Methods:Migration of triple-negative MDA-231 breast cancer cells and its modulation by IGFs, the IGF-1R inhibitor NVP-AEW541 and the IGF-2-sequesteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
(45 reference statements)
0
37
0
Order By: Relevance
“…It has also been shown that high ERβ is expressed in TNBC and associated with worse prognostic outcomes (Hamilton et al 2015). A combination therapy comprising the IGF-2 sequestering antibody MAB292 and topotecan to inhibit the hypoxia-inducible factor-1 enhances the anti-migratory effect of NVP-AEW541 in the TNBC MDA-MB-231 cell line (Mancini et al 2014).…”
Section: Igf1r and Igf2mentioning
confidence: 99%
“…It has also been shown that high ERβ is expressed in TNBC and associated with worse prognostic outcomes (Hamilton et al 2015). A combination therapy comprising the IGF-2 sequestering antibody MAB292 and topotecan to inhibit the hypoxia-inducible factor-1 enhances the anti-migratory effect of NVP-AEW541 in the TNBC MDA-MB-231 cell line (Mancini et al 2014).…”
Section: Igf1r and Igf2mentioning
confidence: 99%
“…Insulin-like growth factor-1 (IGF-1) signaling is associated with various types of cancers, including pancreatic, lung and breast cancers [1315]. Activation of IGF-1 receptor (IGF-1R) by IGF-1 binding results in cell proliferation, metastasis and drug resistance, and it is reported that IGF-1R promotes survival and proliferation of TNBC cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of IGF-1 receptor (IGF-1R) by IGF-1 binding results in cell proliferation, metastasis and drug resistance, and it is reported that IGF-1R promotes survival and proliferation of TNBC cell lines [16]. In fact, targeting IGF-1R inhibited migration and invasion of the TNCB cell line MDA-MB-231 [15]. Furthermore, in vivo experiments have shown that IGF-1R knockdown reduced the potential of MDA-MB-231 cells to establish brain metastases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Along similar lines ALK/IGF1R inhibition was recently described as a new therapeutic approach for lung cancer [77]. Furthermore preclinical studies using cancer cell lines strongly support the rationale for co-targeting IGF1R and HIF1 in breast cancer [78] or IGF1R and c-kit in non-small cell lung cancer [79]. Moreover, treatment of CRPC using a combination of IGF axis inhibitors with new generation AR inhibitors, or with other targeting drugs, awaits evaluation in preclinical and clinical studies.…”
Section: Characteristics Of Clinical Studies Targeting the Igf1r In Pcamentioning
confidence: 83%